Photocatalyst treatment for lead(II) using titanium oxide nanoparticles embedded in PVA-alginate beads - Idris, A. (Taylor and Francis Inc., 2016)
In this paper, titanium oxide nanoparticles were produced using the hydrothermal method and embedded in PVA–alginate beads to remove Pb(II) ions from aqueous solutions. The kinetics of the photocatalyst process was elucidated by varying operating parameters such as pH (3, 7 and 10) and initial Pb(II) concentrations (25, 50, 100 and 200 mg/L). The findings revealed that 99.1% of the Pb(II) was removed within 150 min and maximum removal occurred in initial concentration of 25 mg/L at pH 7. The titania PVA-alginate beads can be readily isolated from the aqueous solutions after the photocatalytic process and reused for at least seven times without significant loss in their initial properties. In addition, the reduction of Pb(II) from wastewater using titania PVA-alginate beads fitted the Langmuir–Hinshelwood kinetic model with a correlation coefficient (R2) of 0.9931. © 2015 Balaban Desalination Publications.